Analisis Dampak Internet of Things (IoT) Pada Perkembangan Teknologi di Masa Yang Akan Datang - Nahdi, Fahad; Dhika, Harry (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2021)
The internet of things (IoT) is common place from day to day. The main purpose of IoT is to connect the physical to digital world. Thus, the physical world is measured by sensors and translated into data that can be read by the computer (digitization), and the data must be translated into instructions to be executed by the actuator (mover). Due to the increasing use of IoT, the number of platforms designed to support IoT has increased significantly. As a result of different standards, approaches and uses, there are a wide range of IoT platforms. this thing raises problems selecting, understanding, and using the appropriate application. In this paper researchers use the library study method of various journals as a source and will explain how Iot will become a technology of the future.